Transformasi Pers Islam di Era Reformasi - Budi Irawanto (Jurnal Ilmu Sosial dan Ilmu Politik, 2006)
The 1998 Reformasi movement has contributed to the blossoming of pers freedom in Indonesia. Consequently, there has been a rapid growth in the number of print media, including the "Islamic press" which claims to represent the interest of the muslim majority. In fact, the Islamic press attracts a diverse readership with a wide variety of demographics such as age, gender, social group and ideology. The growth of the Islamic press is scruntinized in this article to clarify the process of negotiationb between Islamic value, popular culture, mystic traditions and Indonesia contemporary politics. This process of negotiation has become important following the financial bankruptcy of many Islamic media organisations due to mismanagement and changes in the aspirations of Indonesian muslim. This article argues that the econimic and political sustainability of the Islamic press depends on its ability to appropriate popular culture and to articulate the politics of Islam in the context of contemporary Indonesia.